Analisis Pengaruh Lingkungan Keluarga dalam membentuk Karakter Siswa - Agus Faisal Asyha; Al Ikhlas; Trisna Rukhmana; Singgih Prastawa; Aat Ruchiat Nugraha; Joni Wilson Sitopu (Journal on Education, 2024)
This research aims to analyze the influence of the family environment on the formation of student character. In an increasingly complex global era, education is one of the important aspects that influences the formation of students' character. The family environment, which includes the values, norms and behavior adopted by family members, has an important role in forming students' character. This research uses qualitative research methods to understand the phenomenon from the perspective of the subject, namely students and their family environment. The research results show that the family environment has a significant role in shaping student character. Students who grow up in an environment that adheres to positive values ​​tend to have positive and useful characters. This research confirms the importance of the family environment in forming student character and shows that educational strategies that pay attention to the family environment and the values ​​held by the family can help improve learning outcomes and student character.